KONFLIK ANTARA TOKOH MASYARAKAT DENGAN PIMPINAN PONDOK PESANTREN AL-JABALIYYAH BANGKOK NAGARI SILAYANG KECAMATAN MAPAT TUNGGUL SELATAN KABUPATEN PASAMAN - -, Roni - (Pendidikan Sosiologi, 2014)
Conflicts between community leaders with the leaders started boarding school in 2009 by the notion or prejudice between the two sides, and became violent in 2011 with the resistance of the majority of community leaders and a small portion of the youth members of the leadership of the pesantren. This study used a qualitative approach with descriptive type using purposive sampling technique to the data type of primary data and secondary data. Methods of data collection is done in three ways: observation, interview, and document. In accordance with the research objectives, this study describes the: (1). The process of conflict into violence that began in 2009 were characterized by a debate about the distribution of tithes and exploded into violence in 2011 which damage the infrastructure foundation boarding school by a group of youths who successfully influenced provocateur (A / S). (2). Parties to the conflict, namely: (a). Community leaders, (b). Youth groups, (c). Leaders boarding. (3). The cause of the conflict: (a). The division of tithes, (b). Utilization of boarding money for personal gain, (c). Negative bias, (d). Political elements.